Arrhythmia Monitoring for Risk Stratification in Hypertrophic Cardiomyopathy - Darson Du, MD; Christopher O.Y. Li, MD; Kevin Ong, MD; Ashkan Parsa, MD; Adaya Weissler-Snir, MD; Jeffrey B. Geske, MD; Zachary Laksman, MSc, MD, FRCPC (CJC Open, 2022)
Hypertrophic cardiomyopathy (HCM) is the most common inherited cardiomyopathy, presenting significant clinical heterogeneity. Arrhythmia risk stratification and detection are critical components in the evaluation and management of all cases of HCM. The 2020 American Heart Association/American College of Cardiology HCM guidelines provide new recommendations for periodic 24-48-hour ambulatory electrocardiogram monitoring to screen for atrial and ventricular arrhythmias. A strategy of more frequent or prolonged monitoring would lead to earlier arrhythmia recognition and the potential for appropriate treatment. However, whether such a strategy in patients with HCM results in improved outcomes is not yet established. The available evidence, knowledge gaps, and potential merits of such an approach are reviewed. Cardiac implantable electronic devices provide an opportunity for early arrhythmia detection, with the potential to enable early management strategies in order to improve outcomes. RÉsumÉ: La cardiomyopathie hypertrophique (CMH) qui est la cardiomyopathie héréditaire la plus fréquente présente une hétérogénéité clinique importante. La stratification du risque d’arythmies et leur détection sont des composantes essentielles de l’évaluation et de la prise en charge de tous les cas de CMH. Les lignes directrices 2020 de l’American Heart Association et de l’American College of Cardiology en matière de CMH fournissent les nouvelles recommandations sur la surveillance périodique de l’électrocardiogramme ambulatoire de 24-48 heures pour dépister les arythmies auriculaires et ventriculaires. Une stratégie de surveillance plus fréquente et prolongée permettrait de dépister plus précocement l’arythmie et pourrait mener au traitement approprié. Toutefois, il n’a pas encore été établi qu’une telle stratégie chez les patients atteints de CMH entraînait de meilleurs résultats cliniques. Les données probantes actuelles, les lacunes en matière de connaissances et les mérites potentiels d’une telle approche sont passés en revue. Les dispositifs cardiaques électroniques implantables offrent la possibilité de détecter précocement l’arythmie et le potentiel de favoriser des stratégies de prise en charge précoce pour améliorer les résultats cliniques.